Morbidity in elderly with dental loss - Bernardo Ricardo Pérez Barrero; Daniel Enríquez Calas; Cristina Perdomo Estrada; Walkyria de la Caridad González Rodríguez (Centro Provincial de Información de Ciencias Médicas, 2020)
Introduction: Dental loss has consequences in the elderly general physiologic function and appearance, that constitutes an unsolved problem in the Bolivian Republic of Venezuela.  Objective: To describe the morbidity in elderly with loss of permanent teeth.  Method: A descriptive, observational and cross-sectional study was carried out in   Simón Bolívar Clinic from Diego Ibarra municipality, belonging to Carabobo in Venezuela, from January to June, 2016. The universe was constituted by 100 elderly of 60 years and more from both sexes and partially or totally toothless. The analyzed variables were age, sex, oral hygiene, number of lost permanent teeth, as well as the type of prosthesis required. The relative and absolute frequencies were used as summary measures.  Results: It was found that 73.0 % of the elderly lost their teeth due to dental decay, being women and the 60-64 age group the most affected one. Also, the poor oral hygiene and the necessity of partial prosthesis prevailed.  Conclusions: A high morbidity existed in elderly with dental loss, which affected their functionality, aesthetics and self-esteem that could cause important consequences in the oral cavity and in the rest of the body if it is not corrected, without forgetting the prevention or early detection of any other oral disease that generates it.